Pengaruh Kepemimpinan Transformasional Dan Budaya Organisasi Terhadap Kepuasan Kerja Serta Dampaknya Pada Kinerja Karyawan - Rizki Wahyuniardi; Hepytisa Renaldo Nababan (Jurnal Teknik Industri, 2018)
This study aims to analyze employee performance. Employee performance is the result of thinking and energy from an employee to the existing job, can be tangible, seen, employee performance by some factors that are Transformational Leadership, Organizational Culture, and Job Satisfaction. Referring to the purpose of research that is done is to analyze and analyze various variables, then this research is descriptive and verificative. In descriptive analysis explained the dependent variables on which the theory is based. The verification analysis is used. Structural Equation Modeling (SEM) with the help of Lisrel program.